Constantine and the captive Christians of Persia : martyrdom and religious identity in Late Antiquity - Smith, Kyle, 1977- (Transformation of the classical heritage, 2016)
"This book demonstrates that the history of Christianity in the fourth century has been written mainly on the basis of Greek ecclesiastical histories and Syriac martyrdom narratives that date to decades, even centuries, after the fact. By closely analyzing these sources--which often exhibit conflicting religious, political, and hagiographical agendas--an evolving portrait of the first Christian emperor begins to emerge. This portrait of Constantine is useful not for re-constructing the events of the fourth century, but for understanding how the Syriac Christians of Roman Mesopotamia and Sasanian Persia used Constantine and the Christians of the West to fashion multiple political and religious identities over a prolonged period of change"--Provided by publisher